If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-13+57=-4(x+3)
We move all terms to the left:
-13+57-(-4(x+3))=0
We add all the numbers together, and all the variables
-(-4(x+3))+44=0
We calculate terms in parentheses: -(-4(x+3)), so:We get rid of parentheses
-4(x+3)
We multiply parentheses
-4x-12
Back to the equation:
-(-4x-12)
4x+12+44=0
We add all the numbers together, and all the variables
4x+56=0
We move all terms containing x to the left, all other terms to the right
4x=-56
x=-56/4
x=-14
| 12=7x-4 | | 9x-1+5=10 | | |9x-1|+5=10 | | 11x^2+21=7 | | 3n=15-2n | | 11x^+22=7 | | x-23=-9 | | m+7+7=17 | | m+8+3=-30 | | m+8+3=30 | | x+9=10x-15 | | 577x-27-566x+64-37=33 | | x-9=-10x-15 | | 9(x-1)-6=4x+5(-3+x) | | -8+z=2 | | 4(6n-1)+8=6(4n+6) | | 5÷7x+9=78 | | 18-13=1/2a+3/4a+5/8a | | (2+-1)(t+5)=0 | | 2+-1)(t+5)=0 | | (0.75-x)^2÷2x=0.11 | | 0.02(x-1)=-12 | | |x-6|=25 | | 3x2+x=x+243 | | 0=-2x^2+2x | | 2t/7=42/49 | | 3(3n+n)=2(n+5) | | 8(x+1)+4=5x+3(4+x) | | c+22-0.75c=5-0.5c+17 | | 6(9n-1)+7=9(6n+9) | | 4x-5=6x-6 | | 4.2=7t |